Roles of Psychological Flexibility, Parenting Competence, and Asthma Management Self-Efficacy in the Functioning Outcomes of Parents of Children with Asthma Co-Occurring with Attention-Deficit/Hyperactivity Disorder - Yuen Yu Chong; Pui Tik Yau; Joycelyn Yee Man Kwan; Wai Tong Chien (European Journal of Investigation in Health, Psychology and Education)
Asthma and ADHD represent prevalent pediatric conditions, with the former being a physical disorder and the latter being a neurodevelopmental disorder. This study examined the influence of parental psychological flexibility (PF)—the ability to adapt to evolving situational demands, shift perspectives, and balance competing priorities—alongside parenting competence and asthma management self-efficacy on family functioning and parental psychological adjustment in families with children exhibiting concurrent asthma and ADHD symptoms. Baseline data were analyzed from 130 parents (mean age = 40.3 years, SD = 5.5; 88.9% mothers) of children diagnosed with both asthma and ADHD (mean age = 8.0 years, SD = 2.2; 74.6% boys), who were participating in a randomized controlled trial evaluating an Acceptance and Commitment Therapy (ACT)-based parenting intervention. An adjusted structural equation model revealed that greater parental psychological inflexibility was significantly associated with poorer family functioning (β = −0.61, 95% CI [−0.74, −0.33], p < 0.001) and increased psychological maladjustment (β = 0.48, 95% CI [0.32, 0.63], p < 0.001), accounting for intercorrelations with parenting competence and parental asthma management self-efficacy. Additionally, parental psychological flexibility was found to mediate the relationship between parenting competence and both family functioning and psychological adjustment. These findings underscore the importance of targeting parental psychological inflexibility and enhancing parenting competence in interventions to improve family dynamics and parental mental health and thereby suggest a shift from the traditional focus on self-efficacy in symptom management for pediatric asthma and ADHD.